Pengelolaan Arsip Inaktif Sebagai Upaya Mendukung Penyusutan Arsip di Dinas Kependudukan dan Pencatatan Sipil Kota Malang - Muhamad Ilham Purnomo; Diana Eka Poernamawati (Perspektif Administrasi Publik dan hukum, 2025)
Inactive archives are archives that are used infrequently but still have administrative, legal, or historical value, so they must be maintained properly. Management of inactive archives is important so that the stored information is maintained, easily found when needed, and does not cause accumulation that disrupts the efficiency of storage space. This study aims to describe in detail the management of inactive financial archives at the Population and Civil Registration Office (Dispendukcapil) of Malang City and identify the obstacles encountered in the process. The study used a qualitative descriptive method with data collection techniques through direct observation of the archive room, interviews with archive management officers, and document reviews related to management procedures. The results showed that the number of inactive financial archives managed reached 13.4 linear meters. The management process includes the stages of transferring archives from work units to archival units, identifying the type and period of archives, position adjustment maneuvers, data input into a simple system, numbering, storage in archive boxes, labeling, and arranging boxes on storage shelves. Although the management procedures are running, the study found a major obstacle in the form of the absence of an Archive Retention Schedule (JRA) specifically for financial archives. This prevents the archives reduction process from being carried out legally and in a planned manner, resulting in a buildup of archives, which reduces storage capacity and potentially makes information retrieval difficult. This study recommends the development of a Financial Archives Retention Schedule (JRA) specifically for financial archives that complies with statutory provisions and agency needs, so that the reduction process can be carried out systematically, efficiently, and accountably. The implementation of the JRA is also expected to improve the effectiveness of archives management and support public service performance at the Malang City Population and Civil Registration Office (Dispendukcapil).